Implementasi Prinsip Komunikasi Islam dalam Interaksi Keluarga Masyarakat Suku Karo di Desa Budaya Lingga Kecamatan Simpang Empat Kabupaten Karo - Siti Rahmawati; Rubino Rubino (LPPM Institut Nasional Laa Roiba Bogor, 2024)
As social beings, of course humans cannot be separated from interactions that require communication in the process. In the process of social interaction, culture and customs also have a contribution in regulating the principles of communication. The principle of communication basically plays an important role for indigenous peoples because it can become a control tool in communicating in everyday life. The phenomenon of the Karo community also has various rules in interactions with both family and society. There are several rules of interaction in the communication of the Karo people which are in line with the principles of Islamic communication. So this paper aims to find out how to implement the principles of Islamic communication in family interactions with the Karo people in the Lingga Cultural Village, Simpang Empat District, Karo Regency. This type of research is a descriptive qualitative research that describes how the implementation of the principles of Islamic communication in the interaction of families of the Karo people. The data collection techniques used in this study were observation/field research, interviews, and literature studies by collecting references obtained from books and journals that support this research. The results of the study show that in family interactions, the Karo people also use the principles of Islamic communication, namely qoulan karima in interactions with parents, and interactions between in-laws and in-laws which are included in the rebu tradition in the Karo tribe, namely mehangke (reluctance and respect). . In interactions with others and relatives, this interaction is in line with the principles of Islamic communication, namely qoulan ma'rufa by prioritizing interactions using good language and appropriate expressions. Keywords: Islamic communication principles; family interactions; the Karo tribe;